PENGARUH KEPEMILIKAN SAHAM MAYORITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN FARMASI (STUDI PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI TAHUN 2015-2019) - Salsabila Salsabila; Urip Santoso (Business Administration Department - Universitas Katolik Parahyangan, 2021)
The majority shareholder has the absolute right to appoint or to influence the appointment of company's top management officials, to make decision, and to access company's information. Company performance is the benchmark for a company to achieve its goals. This research aims to determine the condition of majority share ownership, the condition of financial performance, and the influence of majority share ownership to the financial performance of pharmaceutical companies listed on the Indonesia Stock Exchange in 2015-2019. This research was conducted on 8 pharmaceutical companies listed on the Indonesia Stock Exchange in 2015-2019. This research uses quantitative, hypothetical-deductive method. The data collection technique used is the unobtrusive method. This research uses descriptive analysis and simple linear regression. This research examines the effect of majority share ownership on the financial performance of pharmaceutical companies as measured by the ratio of sales growth, return-on-assets, return-on-equity, earnings-per-share growth, and price-to-book value. The results show that majority share ownership only had a significant effect on the growth of earnings-per-share and price-to-book value. GCG principles are very important and need to be applied to companies. Every role of a company must be able to carry out its functions based on their respective rights and responsibilities.